2017
DOI: 10.1108/ijaim-06-2016-0067
|View full text |Cite
|
Sign up to set email alerts
|

Product market competition, R&D investment choice, and real earnings management

Abstract: Purpose Recent studies in the accounting literature have investigated the economic consequences of R&D capitalization. Discretionary R&D capitalization for target beating can be characterized as a firm signaling private information on its future economic benefits or as opportunistic earnings management. R&D capitalization also has an impact on a firm’s marginal costs and product market competition. The purpose of this paper is to address how firms choose R&D levels for the purpose of meeting or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
1
4
0
2
Order By: Relevance
“…It extends and generalizes the findings to emerging market as restrictively reported in the USA and UK from 1978 to 2007 by Anagnostopoulou (2008). The paper also complements Hsiao et al (2017) paper that reports higher R&D and higher accounting performance in terms of profits and earnings. It also supports the results by Isaboke and Chen (2019) with a specific IFRS-like R&D standard.…”
Section: Evidence From Chinasupporting
confidence: 80%
See 1 more Smart Citation
“…It extends and generalizes the findings to emerging market as restrictively reported in the USA and UK from 1978 to 2007 by Anagnostopoulou (2008). The paper also complements Hsiao et al (2017) paper that reports higher R&D and higher accounting performance in terms of profits and earnings. It also supports the results by Isaboke and Chen (2019) with a specific IFRS-like R&D standard.…”
Section: Evidence From Chinasupporting
confidence: 80%
“…Similar results are reported by Zhu et al (2017) that the positive relationship between R&D intensity and firm performance is stronger for China’s better-performed electronics manufacturing firms. Hsiao et al (2017) found that overinvest in R&D help to earn a higher profit and reach the earnings target. Recently, Jeny and Moldovan (2022) find higher value relevance of capitalized than expensed R&D.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior studies provide evidence of the existence of RAM (Roychowdhury, 2006; Baber et al , 1991; Bartov, 1993; Bens et al , 2002; Hsiao et al , 2017; Nasir et al , 2018). Roychowdhury (2006) developed empirical measures to proxy for RAM of discretionary expenses and reports that managers avoid reporting losses by undertaking RAM.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Gunny (2010) provides evidence that managers cut discretionary spending and use sales manipulation and overproduction to meet or beat earnings targets. Hsiao et al (2017) reports that a firm can manage to meet earnings benchmarks by adjusting its R&D choices. Abernathy et al (2014) suggests that management engages less in RAM when a firm is constrained by poor financial conditions, high levels of institutional ownership and low industry market share.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…‫بمنشآت‬ ‫المحيطة‬ ‫والخارجية‬ ‫الداخلية‬ ‫األعمال‬ ‫بيئة‬ ‫على‬ ‫دراماتيكية‬ ‫تغيرات‬ ‫كورونا‬ ‫لجائحة‬ ‫الفجائية‬ ‫الطبيعة‬ ‫أحدثت‬ ‫وقد‬ ‫هذا،‬ ‫األعمال‬ (Ding , et al, Watts & Zimmerman, 1986;Gaver, et al, 1995;Lassoued & Elmir, 2012;Ben rejeb, et al, 2013;Lassoued, 2021;Taylor, et al, Choi, et al, 2011;Walker, 2013;Ozili, 2017) . Kousenidis, et al, 2013;Filip & Raffournier, 2014;Cimini, 2015 Aljawaheri, et al, 2021;Xiao & Xi, 2021;Yan, et al, 2022;Aljughaiman, et al, 2023;Taylor, et al, (Walker, 2013;Cimini, 2015;Kim, et al, 2018;He & Jianqun, 2021;Chen, et al (Chi et al, 2011;Ho, et al, 2015;Xu & Ji, 2016;Hsiao, et al, 2017;Kjaerland, et al, 2021 ‫التنبؤية‬ ‫قدرتها‬ ‫من‬ ‫ويزيد‬ ‫عنها،‬ (e.g. Choi, et al, 2011;Walker, 2013;Ozili, 2017) .…”
unclassified